Crop rotation and cultivation effects on Convolvulus arvensis population dynamics in small grain organic cropping systems - Hettinger, Kara; Miller, Zach; Hubbel, Kyrstan; Seipel, Tim (Frontiers in Agronomy, 2023)
Convolvulus arvensis L. Scop. (field bindweed) is a difficult weed to manage in organic cropping systems. Convolvulus arvensis suppression often requires intensive tillage and cultivation practices that have negative impacts on soil quality. To improve C. arvensis management in organic, small grain cropping systems, we compared ten cropping system treatments in a field trial from the autumn of 2017 until harvest of 2020 in Corvallis, MT, USA. Cropping system treatments varied along a gradient of tillage and crop competition, with tillage intensity and competition inversely related. High soil disturbance and no competition occurred in two treatments that remained in tilled fallow for two consecutive years. Six cropping system treatments had different combinations of tillage and annual or biennial crops, including wheat and forages. Two treatments had minimal soil disturbance and maximum competition from two consecutive years of perennial alfalfa. Convolvulus arvensis ramet density was counted annually to estimate changes in treatments over time. Differences in soil chemical and physical properties between treatments were also assessed in the final years of the study. In the first two years, there was no difference in C. arvensis ramet density among cropping system treatments. In the final two years of the study, C. arvensis density remained below one ramet per m2 in intensively tilled fallow treatments and perennial alfalfa treatments, but was much more variable in treatments with more diverse annual and biennial crop rotations with minimal to moderate tillage. The only differences between treatments in soil physical and chemical properties was aggregate stability. Soil from the most intensively tilled fallow treatments had lower soil aggregate stability than six other treatments, indicating higher erosion potential. Our results suggest that annual cropping systems can lead to increased C. arvensis density. Incorporating a perennial forage or an intensively tilled fallow period can prevent C. arvensis expansion in small grain organic cropping systems, but the perennial forage can protect and enhance soil quality.